Psychological factors and their impact on criminal behavior - challenges of combating Crime with a psychological factor – - Benterki, Leila (Journal of Human Sciences, 2021)
Social theories help us identify crime as a general social phenomenon and try to highlight some of the causes and motives of crime, but criminologists do not stop their scientific efforts at this point, but rather think that crime is of a complex nature. It can only be studied and its causes can be found if we highlight the human, sensational and non-sensational facets that lead to crimes, the importance of criminal psychology and the psychological aspects of the criminal, and this study will be based on the descriptive, analytical and deductive methods. To conclude after analysis and discussion the theoretical and scientific benefits of psychology, its relationship to crime and its impact on human behavior, criminal scientists and psychologists agree that the study of crime as an individual phenomenon is based on these characteristics, whether it is a state of social incompatibility or a state of inconsistency.